Chinese university students’ preferences for physical activity incentive programs: a discrete choice experiment - Zhang, Jingbo; Li, Qing; Zhang, Jinzi; Zhao, Xianqi; Jiang, Maomin; Huang, Xincheng; Liu, Diyue; Yan, Yupei; Li, Xialei; Chen, Jiangyun; Ma, Zheng Feei; Zhang, Xiyue; et al. (Frontiers in Public Health, 2023)
Purpose This study aims to explore and compare Chinese university students’ preferences for various physical activity motivation programs. Patients and methods A cross-sectional study was conducted in China from February 25 to March 25, 2022. Participants anonymously completed an online questionnaire based on a DCE. A total of 1,358 university students participated in the survey. The conditional logit model (CLM), willingness to accept (WTA), and propensity score matching (PSM) were used to assess college students’ preferences for different attributes and levels of physical activity incentive programs. Results Respondents identified the number of bonus, exercise time, and academic rewards as the three most significant attributes of the athletic incentive program. The importance of each attribute varied based on individual characteristics such as gender and BMI. In CLM, college students displayed a preference for a “¥4” bonus amount (OR: 2.04, 95% CI 1.95–2.13), “20 min” of exercise time (OR: 1.85, 95% CI 1.79–1.92), and “bonus points for comprehensive test scores” as academic rewards (OR: 1.33, 95% CI 1.28–1.37). According to the WTA results, college students were willing to accept the highest cost to obtain academic rewards tied to composite test scores. Conclusion The number of bonus, exercise time, and academic rewards emerge as the three most crucial attributes of physical activity incentive programs. Furthermore, college students with different characteristics exhibit heterogeneity in their preferences for such programs. These findings can guide the development of programs and policies aimed at motivating college students to engage in physical activities.